2013
DOI: 10.33225/jbse/13.12.249
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Secondary Science Teachers’ Images About Themselves as Science Teachers

Abstract: The purpose of this study is to explore pre-service secondary science teachers’ images of themselves as science teachers. Also, the association between instructional style, and domains was explored. 130 secondary science teachers (biology, chemistry and physics) from 26 public universities participated in the data collection for this study. The Draw a Science Teacher Test Checklist (DASTT-C) was used as a data collection instrument. The results of study showed that pre-service science teachers’ images is 24.62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…After the research activities, it was seen that there was no pre-service chemistry teacher with a teacher-centered image among the pre-service chemistry teachers who participated in the research activities. The fact that pre-service chemistry teachers have a student-centered image after the research activities can be explained by the fact that pre-service chemistry teachers are more willing to student-centered education (Akkuş, 2013). Markic and Eilks (2013) stated that in the first year of their education, pre-service chemistry teachers are teacher-centered; In the middle and at the end, they concluded that they have a student-centered image (exploratory teaching style).…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the research activities, it was seen that there was no pre-service chemistry teacher with a teacher-centered image among the pre-service chemistry teachers who participated in the research activities. The fact that pre-service chemistry teachers have a student-centered image after the research activities can be explained by the fact that pre-service chemistry teachers are more willing to student-centered education (Akkuş, 2013). Markic and Eilks (2013) stated that in the first year of their education, pre-service chemistry teachers are teacher-centered; In the middle and at the end, they concluded that they have a student-centered image (exploratory teaching style).…”
Section: Results Discussion and Recommendationsmentioning
confidence: 99%
“…Araştırma etkinlikleri sonrasında araştırma etkinliklerine katılan kimya öğretmen adaylarından, öğretmen merkezli imaja sahip kimya öğretmen adayının olmadığı görülmüştür. Araştırma etkinlikleri sonrasında kimya öğretmen adaylarının öğrenci merkezli imaja sahip olmaları, kimya öğretmen adaylarının öğrenci merkezi eğitime daha istekli olmaları (Akkuş, 2013) öğretmen hem de öğrenci merkezli imajlara sahipken, imajlarının yıldan yıla değiştiği ve dördüncü yılda hem öğretmen hem de öğrenci merkezlerin imajlarının yanında öğrenci merkezli imaja sahip öğretmen adayı sayısının arttığı sonucuna ulaşmıştır. Bunun yanında pedagojik alan ile ilgili yapılan etkinlikler öğretmen adaylarının kendilerine yönelik imajlarını etkilemektedir ve özellikle öğretmen adaylarının imajlarını öğrenci merkezli bir yönelime kaydırmaktadır, (Scharfenberg & Bogner, 2016).…”
Section: Veri Toplama Araçları Ve Verilerin Analiziunclassified
“…Recently, pre-service teacher training has been under researchers' microscope from several angles. It is for example their images about themselves as teachers (Akkus, 2013), the effect of micro-teaching (Komolafe et al, 2020), or paired peer approach on their development (Lewis et al, 2021). PSTs' training has also been focusing on their ability to notice-on the students' professional vision development as well as ways to foster it (Janík et al, 2019;Rusek et al, 2016;Simpson et al, 2018).…”
Section: Introductionmentioning
confidence: 99%